Daunorubicin and doxorubicin but not BCNU have deleterious effects on organotypic multicellular spheroids of gliomas - Kaaijk, P; Troost, D; de Boer, O J; Van Amstel, P; Bakker, P J; Leenstra, S; Bosch, D A (British journal of cancer, 1996)
In the present study organotypic multicellular spheroids (OMS) were used to study the effects of chemotherapeutic agents on malignant gliomas. Compared with the frequently used cell line models, OMS have several advantages with respect to the preservation of the cellular heterogeneity and the structure of the original tumour. OMS prepared from seven glioma specimens were treated with 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU), daunorubicin or doxorubicin. After exposure to these drugs, the histology and cell proliferation of the OMS were analysed by immunohistochemistry and image analysis. Furthermore, the expression of P-glycoprotein (P-gp) and multidrug resistance-related protein (MRP), which both can contribute to resistance to daunorubicin and doxorubicin, were immunohistochemically investigated. We found that OMS from gliomas are sensitive for daunorubicin and doxorubicin but not for BCNU in terms of tissue destruction and decrease in cell proliferation. In addition, all gliomas were P-gp and MRP negative, which is in accordance with the sensitivity for daunorubicin and doxorubicin. Considering the potential use of several new alternative drug delivery methods, such as intratumoural implantation of drug-impregnated polymers or liposomal encapsulation of cytostatic drugs, daunorubicin and doxorubicin might be effective in the treatment of malignant gliomas.